FREE CASH FLOW SEBAGAI PEMODERASI PENGARUH EARNINGS MANAGEMENT DAN KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN - Dewi, Ida Ayu Made Chandra; Putra, I Wayan (E-Jurnal Akuntansi, 2017)
A firm was found to maximize profit that increases the firm value. This research has some purpose there are to give empircal proof about earnings management and dividend policy an affect firm value that listed at LQ45 with moderating variabel that is free cash flow. This study has 60 observation that choosen by applying non probability method and purposive sampling technique. In processing data, Moderated Regression Analysis (MRA) is applied as data analysis technique. The result founded that earnings management has a negatif significant influence on firm value, dividend policy has a negatif significant influence on firm value, the influence of earnings management on firm value is weaken by free cash flow, and the influence of dividend policy on firm value is weaken by free cash flow.
Keywords: LQ45, firm value, earnings management, dividend policy, free cash flow